Penyuluhan Perizinan Nomor Induk Berusaha (NIB) dan Izin Edar Produk Makanan bagi Pelaku UMKM di Kalurahan Wukirsari, Imogiri, Yogyakarta. - Masrukan; Darmawan, Eman; Fiersta, Nissa Clara; Tunnisa, Fitra; Gorotomole, M. Alamin (Universitas Widya Mataram, 2024)
Small home industries play an important role in the regional economic hierarchy, especially in BantulRegency, Special Region of Yogyakarta (DIY). A total of more than 100 food SMEs are stillexperiencing problems related to licensing in establishing a business, guidelines for good and correctfood production, diversification of food processing, and business legality which includes licensing,product distribution permits and marketing. In addition, there are several business actors who havenot obtained NIB, so it is necessary to make efforts to understand the information. The persuasiveapproach method is carried out to provide information on how to produce good processed food, halalfood product certification, food diversification and business legality for food SME actors. Throughtraining and technical guidance on how to obtain certification and business feasibility from theauthorized government, so that SME actors can improve social, economic and cultural welfareindependently.